Metabolic Syndrome May Not be a Good Predictor of Coronary Artery Disease in the Iranian Population: Population-Specific Definitions are Required - Mahmoud Ebrahimi; Seyyed Mohammad Reza Kazemi-Bajestani; Majid Ghayour-Mobarhan; Mohsen Moohebati; Roghaye Paydar; Mohsen Azimi-Nezhad; Habib Ollah Esmaily; Gordon A. A. Ferns (The Scientific World Journal)
Metabolic syndrome (MS) is associated with an increased risk of coronary artery disease (CAD) in Western populations. We have investigated the relationship between the presence of MS and other conventional risk factors, and angiographically defined CAD, in a Middle Eastern population. Patients (n = 431) attending a hospital cardiology clinic for angiography were assessed. Each patient subsequently underwent routine angiography. Anthropometric and biochemical data were used to establish whether patients had MS, using either IDF or NCEP-ATP III criteria. The relationship between the presence of MS, or other individual coronary risk factors, and angiographically defined CAD was assessed by logistic regression analysis. A further reference group of individuals without overt CAD (n = 1276) was used as an additional comparator group. Of the 431 patients, 327 (75.9%) were found to have angiographically defined CAD. There was no significant relationship between MS, using either the IDF or NCEP-ATP III definitions, and CAD in this population. Of the parameters assessed, age, total cholesterol, and low serum HDL cholesterol were the strongest independent predictors of angiographically defined CAD (p < 0.01, p < 0.01, p < 0.05, respectively). It appears that within an Iranian population, the presence of MS defined by either the NCEP-ATP III or IDF criteria fails to identify individuals with established, angiographically defined CAD. However, a low serum HDL cholesterol, a component of MS, was an important independent predictor of CAD in this population. It is possible that the criteria for defining MS as a risk predictor of CAD in Middle Eastern populations may need to be revised.